2022
DOI: 10.3390/nu14163264
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dietary Total Antioxidant Capacity and the Prognosis of Amyotrophic Lateral Sclerosis

Abstract: Antioxidant intake has been suggested to be associated with the prognosis of amyotrophic lateral sclerosis (ALS). This study aimed to investigate whether dietary total antioxidant capacity (DTAC) and that of major food groups are related to disease progression rate (ΔFS) and survival time in ALS patients. A total of 301 participants diagnosed with sporadic ALS according to the revised El Escorial criteria were recruited from March 2011 and followed up to the event occurrence, or the end of October 2021. Events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Eom et al showed antioxidants might be effective in delaying ALS progression and increasing the life expectancy of patients [ 84 ]. Cellular oxidation processes play a role in ALS, and antioxidant agents are promising for the treatment of ALS [ [85] , [86] , [87] ].…”
Section: Clinical Trial Studiesmentioning
confidence: 99%
“…Eom et al showed antioxidants might be effective in delaying ALS progression and increasing the life expectancy of patients [ 84 ]. Cellular oxidation processes play a role in ALS, and antioxidant agents are promising for the treatment of ALS [ [85] , [86] , [87] ].…”
Section: Clinical Trial Studiesmentioning
confidence: 99%